ASSESSMENT OF PERIPHERAL RETINAL LESIONS IN THE SECOND EYE OF PATIENTS WITH PRIMARY RETINAL DETACHMENT: CLINICAL CASES REPORT (Vietnam Journal of Community Medicine, 2026)
Objective: Primary retinal detachment is a severe ophthalmic condition and one of the major causes of vision loss if not treated promptly. Early detection and treatment of peripheral retinal dengeration in the fellow eye of patients with primary retinal detachment are of great importance and should be routinely screened.Method: We described three cases of patients who presented with retinal detachment, in whom peripheral retinal dengeration were detected in the fellow eye. Through a comprehensive examination and careful evaluation of the contralateral eye, we identified peripheral retinal degenerations with a high risk of future retinal detachment. The patients subsequently underwent timely prophylactic laser photocoagulation.Results: Timely detection and prophylactic treatment in three patients helped reduce the risk of future retinal detachment.Conclution: Optimal management of retinal detachment cases extends beyond the surgical correction of the affected eye. Comprehensive, periodic screening and examinations, coupled with appropriate prophylactic intervention for the fellow eye, are paramount in preserving long-term visual acuity and enhancing the patient's quality of life.
Keywords: Peripheral retinal degeneration, primary retinal detachment.